Ginsenoside Rg3 inhibits melanoma cell proliferation through down-regulation of histone deacetylase 3 (HDAC3) and increase of p53 acetylation. - Xiu Shan; Yuan-Shan Fu; Faisal Aziz; Xiao-Qi Wang; Qiu Yan; Ji-Wei Liu (PLoS ONE, 2014)
Malignant melanoma is an aggressive and deadly form of skin cancer, and despite recent advances in available therapies, is still lacking in completely effective treatments. Rg3, a monomer extracted from ginseng roots, has been attempted for the treatment of many cancers. It is reported that the expressions of histone deacetylase 3 (HDAC3) and p53 acetylation correlate with tumor cell growth. However, the antitumor effect of Rg3 on melanoma and the mechanism by which it regulates HDAC3 expression and p53 acetylation remain unknown. We found high expression of HDAC3 in human melanoma tissues to be significantly correlated to lymph node metastasis and clinical stage of disease (p<0.05). In melanoma cells, Rg3 inhibited cell proliferation and induced G0/G1 cell cycle arrest. Rg3 also decreased the expression of HDAC3 and increased the acetylation of p53 on lysine (k373/k382). Moreover, suppression of HDAC3 by either siRNA or a potent HDAC3 inhibitor (MS-275) inhibited cell proliferation, increased p53 acetylation and transcription activity. In A375 melanoma xenograft studies, we demonstrated that Rg3 and HDAC3 short hairpin RNA (shHDAC3) inhibited the growth of xenograft tumors with down-regulation of HDAC3 expression and up-regulation of p53 acetylation. In conclusion, Rg3 has antiproliferative activity against melanoma by decreasing HDAC3 and increasing acetylation of p53 both in vitro and in vivo. Thus, Rg3 serves as a potential therapeutic agent for the treatment of melanoma.